Ruins and residues in Tierra Amarilla by Germán Marín and Nuestra parte de noche by Mariana Enríquez - Ruiz Figueroa, Carlos Enrique (2022)
Some novels of the last decade give an account of the historical and political background of the dictatorships and post-dictatorships of Chile and Argentina. These are poetics that expose the sociopolitical vileness using violence and the persistence of evil by hegemonic powers in full democracy in these countries. Based on the above, this article examines the novels Tierra Amarilla (2014) by Germán Marín and Nuestra parte de noche (2019) by Mariana Enríquez as expressions of a process of degradation of the characters from the physical to the mental level, from the actions of agents of evil —humans and metaphysical forces— in corrupted societies and ruinous landscapes, in which the resource of myth appears as a geopolitical strategy of said agents to maintain and validate their hegemonic power, provoking an unpredictable and unstable character in the characters when they advance to a ruinous terminal state, that is, to a corrosive condition of toxic residues that causes damage through passive action of criminal complicity in Tierra Amarilla, and active action perpetrated through violence in Nuestra parte de noche.